Monitoring linear accelerator beam with daily quality assurance phantom - Dhoju, Nirajana; Pudasainee, Asmita; Jha, Bidhyapati; Yadav, Pramod Kumar; Pokharel, Ashok; Nyaichai, Kanchan; Lamichhane , Tika Ram (Scientific World, 2023)
This paper aims to analyze the output constancy of a medical linear accelerator using PTW, and to study the suitability as a daily quality assurance device. It is assumed that the device is sensitive enough to detect minor variations in central axis beam, flatness, symmetry, and beam quality factor. PTW, QUICKCHECKwebline is the most efficient wireless device used in daily quality assurance. The measurements of output doses of photons ( 6MV and 15 MV) and electrons (6,9,12, and 15MeV) from a medical linear accelerator before the daily treatment have been graphically analyzed. This study assures the output stability of Varian Clinac iX 2100 CD linear accelerator at Bhaktapur Cancer Hospital, Bhaktapur, Nepal. The beam flatness, symmetry, beam quality factor, and central axis of photon and electron beam have been analyzed for 10x10cm2 and 20x20cm2 field size in separate ways. Among the measurements, observed parameters lie under the tolerance limit as recommended by American Association of Physicists in Medicine viz. ±3%. The outcomes of the measurements are in the acceptable range for the treatment procedure of patients.